1983
DOI: 10.1016/0304-3959(83)90081-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of follow-up studies of multidisciplinary pain units

Abstract: Chronic pain is a major public health problem in the United States. Estimates from the National Institutes of Health put the cost of chronic pain at 40 billion dollars a year. They estimate that as many as 15 million adults suffer from low back pain with a minimum cost of 5 billion dollars in direct medical costs and 93 million work days lost every year. In an attempt to cope with this massive problem, multidisciplinary pain units have arisen which attempt to address the complex, multi-faceted aspects of a chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(28 citation statements)
references
References 14 publications
1
22
0
5
Order By: Relevance
“…Since Fishbain et al (1993), the number of pain treatment outcome studies stands at more than 300. This extensive literature has been reviewed by numerous authors (White & Harth 1996;Bendix et al, 1996;Koes et al, 1996;Manniche, 1995;Aronoff et al, 1982Aronoff et al, , 1988Wells & Miles, 1991). Unfortunately, the conclusions about the efficacy of pain facility treatment on chronic pain or the efficacy of specific pain treatments is not …”
Section: Outcome Research In Pain Facilitiesmentioning
confidence: 97%
“…Since Fishbain et al (1993), the number of pain treatment outcome studies stands at more than 300. This extensive literature has been reviewed by numerous authors (White & Harth 1996;Bendix et al, 1996;Koes et al, 1996;Manniche, 1995;Aronoff et al, 1982Aronoff et al, , 1988Wells & Miles, 1991). Unfortunately, the conclusions about the efficacy of pain facility treatment on chronic pain or the efficacy of specific pain treatments is not …”
Section: Outcome Research In Pain Facilitiesmentioning
confidence: 97%
“…Most studies on the effects of behavioural programmes still lack adequate follow-up data. Aronoff, Evans and Enders (1983) have looked at follow-up studies of pain units and found the results to be generally positive but methodologically problematic. The methodology, in general, suffered from the usual problems in follow-ups such as low return rates, non-blind ratings, and exclusive dependence on global ratings.…”
Section: Introductionmentioning
confidence: 97%
“…Chronic low back pain · Multimodal treatment program · Prognosis · Social and health care system Problemstellung Seit dem Entstehen von multidisziplinären Schmerzkliniken vor allem in den USA wurde eine Fülle von Erfahrungsberichten der Behandlung von subakuten und chronischen Rücken-schmerzen veröffentlicht [2,6,9,10,11,12,20,25,28,29,31,41,45,46,47].…”
Section: Introductionunclassified